Postnatal development of upper digestive tract in the Duck - Shyla Paulose (Department of Anatomy, College of Veterinary and Animal Sciences, 1990)
The structure and postnatal development of the upper digestive tract of ducks at different stages of growth was studied using 72 white pekin ducklings aged from day-old to 180 days for the proper understanding of their functional peculiarities. The growth, morphology and histology of the tongue, pharynx, oesophagus and crop, proventriculus and gizzard were studied using six birds at each age group. The oesophagus and the gizzard attained the maximum growth by 75 days whereas the tongue, pharynx, and the proventriculus at 150 days of age.